ANALISIS KONFLIK ANTARA BIROKRASI DENGAN WALIKOTA TEGAL PERIODE 2014-2019 - Levi Wiliantoro .; Turtiantoro . .; Koeshandajani . . (Journal of Politic and Government Studies, 2017)
ABSTRACTTitle : Analysis of Conflict Between Bureaucracy with Mayor of Tegal Period 2014-2019Writer : Levi WiliantoroNIM : 14010112110151department : Government and PoliticsBureaucracy and politics are two things that can not be separated, both affect each other in running the government. Political focus on the creation of a public policy while the bureaucracy to focus on implementation. The relationship is often one of the causes of conflict between them. On April 4 2015 the conflict between bureaucracy with Mayor of Tegal out on the surface, after the bureaucrats conduct hearings with the DPRD of Tegal related to rejection of the leadership of Mayor. The purpose of this study was to determine the types, causes, impacts, and the resolution of the conflict between bureaucracy with Mayor of Tegal period 2013-2019. In this study, researchers used the theory of conflict analysis of Fisher as a practical process to assess and understand the reality of conflict from different angles, then this understanding forms the basis for developing the strategy and plan of action. This study used qualitative methods, using information from the bureaucrats of the conflict and the third party in the resolution of the conflict, the Central Java Provincial Government and the State Administrative Court Semarang. The results of this study indicate that the conflict falls into destructive conflict. Factors causing this conflict is the polarization of the conflict between the Mayor with his Deputy, an alleged practice of shadow state in Tegal City Government, and the arrogance of the Mayor in her leadership. Conflict resolution is done through both sides of the conflict and third parties. The study was formulated some recommendations that are expected to assist local governments in Indonesia in managing the conflict between the bureaucracy with the Mayor.Key Words : Conflict Analysis, Conflict Management, Bureaucracyix